Design, fabricate, and performance study of an exhaust heat-driven adsorption air-conditioning system for automobile - Leo, Sing Lim. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Adsorption colling systems powered by waste heat or solar heat can help to reduce the use of ozone depletion substances, such as chlorofluorocarbons (CFCs) and hydro-chlorofluorocarbons (HC FCs). In recent years, this system has witnessed an increasing interest in many fields due to the fact that this system is quiet, long lasting, cheap to maintain an environmental friendly. In this research work, a novel prototype of automobile adsorption air-conditioning system powered by exhaust heat has been successfully built and tested in laboratory. The working pair used is local produce palm-derived activated carbon and methanol, where activated carbons act as an adsorptive substance and methanol as refrigerant. This system consists of two adsorbers, a blower, evaporator with a blower, expansion valve, a condenser with a fan, valves, and engine and some pipe connectors. Two identical adsorbers were constructed and operated intermittently to provide continuously cooling effect. The conclusion drawn from the current work is that the adsorption technology, as prescribed in this work, is feasible and promising for automobile air-conditioning purpose; however, there is a need to further enhance the efficiency and the associated control system for effective on-the-road application.